THE IMAGES OF A WAR ROUTINE (BASED ON BRUCE BAIRNSFATHER'S PAINTINGS) - D. S. Tkachenko (Гуманитарные и юридические исследования)
The article highlights the so-called military anthropology approach to war events studying. It focuses on the author's translations of original English sources related to the British cartoonist Bruce Bairnsfather. His heritage in a form of records and pictures giving his account of life at the front in the first winter (1914-1915) of the First World War, can provide ground for studying not only the War operations themselves, but the evidence of the everyday life routine in trenches.